2014
DOI: 10.6061/clinics/2014(03)06
|View full text |Cite
|
Sign up to set email alerts
|

Association of glucocorticoid receptor polymorphisms with clinical and metabolic profiles in polycystic ovary syndrome

Abstract: OBJECTIVES:We aimed to investigate whether glucocorticoid receptor gene polymorphisms are associated with clinical and metabolic profiles in patients with polycystic ovary syndrome. Polycystic ovary syndrome is a complex endocrine disease that affects 5-8% of women and may be associated with metabolic syndrome, which is a risk factor for cardiovascular disease. Cortisol action and dysregulation account for metabolic syndrome development in the general population. As glucocorticoid receptor gene (NR3C1) polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…29 The BclI variant is also associated with a lower frequency of insulin resistance in women with polycystic ovary syndrome. 30 These facts may support the hypothesis that BclI polymorphism has negative metabolic implications. The clinical significance of screening glucocorticoid gene polymorphism may be useful for identifying subgroups of patients at-risk who would benefit the most from personalized treatment.…”
Section: Polymorphism Bclisupporting
confidence: 73%
“…29 The BclI variant is also associated with a lower frequency of insulin resistance in women with polycystic ovary syndrome. 30 These facts may support the hypothesis that BclI polymorphism has negative metabolic implications. The clinical significance of screening glucocorticoid gene polymorphism may be useful for identifying subgroups of patients at-risk who would benefit the most from personalized treatment.…”
Section: Polymorphism Bclisupporting
confidence: 73%
“…Previous studies have shown a clear association of overweight/obesity with the pathophysiology of PCOS 30–32 . Increased BMI, especially when associated with central obesity, is linked to insulin resistance and compensatory hyperinsulinemia, ovulatory dysfunction, metabolic syndrome, and increased cardiovascular risk 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a clear association of overweight/ obesity with the pathophysiology of PCOS. [30][31][32] Increased BMI,…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of studies on Brazilian populations. Seven studies were from the Northeast region [23][24][25][26][27][28][29], thirteen studies were from the Southeast [30][31][32][33][34][35][36][37][38][39][40][41][42], five studies were from the South [43][44][45][46][47], and two studies were from the Midwest region [48,49]. No data from the North region were available.…”
Section: Discussionmentioning
confidence: 99%
“…Another one study was excluded from the meta-analyses because the control group included participants who were hirsute or had irregular menses [36]. Two studies in which data on PCOS participants were presented only as PCOS phenotypes [35,43] and other two studies that did not present SD values for the variables of interest [29,34] were equally excluded from the meta-analyses. In Brazilian women with PCOS, BMI ranged from 24.2 to 31.9 kg/m 2 ( Table 2).…”
Section: Discussionmentioning
confidence: 99%